Leisure and men's participation in elderly groups of Florianópolis (SC): reasons and meanings - Santos, Priscila Mari dos (2015)
This survey was carried out in order to analyze leisure and participation of older men in five Elderly Groups of Florianópolis (SC). Issues of Elderly men entrance, remain, established relationships with other group members, and the meaning they give to their participation were evaluated. Thirty eight men participated in the study. Interviews and observations were used. Men seek the groups for leisure and social relations. The reasons for remaining were focused on friendships. Multiple meanings were attributed to participation in the groups.